‘Dealing with the western intellectual heritage’: Reading twentieth-century English Literature in light of Alwani’s Sixth Discourse - Hasan, Md. Mahmudul (2017)
Before English literature was given institutional prominence as a subject of study in the colony, Christian missionary activities – that combine religious and educational endeavors – had been used as a tool to desensitize the colonized to the horrors and dehumanizing effects of colonial expansionism. Later, as Terry Eagleton maintains, religion was replaced by English literature as a dominant instrument of “social control.” Hence, even though with ‘decolonization’ the formal colonial mode of subjugation ended and the forces of Christian missionary significantly abated, the discourse of English literature has remained a powerful vehicle of cultural imperialism. As John McLeod (2000:140) argues, “[T]he teaching of English literature in the colonies must be understood as part of the many ways in which Western colonial powers such as Britain asserted their cultural and moral superiority while at the same time devaluing indigenous cultural products.” Twentieth-century Europe was a breeding ground for radical ideologies, such as, “Marxism [… and] other liberal, positivistic, or secular western schools of thought” (Alwani, 1995:87). Driven by the philosophy of dialectical materialism, European intellectuals seemed to have supposed “themselves divine and answerable to no one but themselves [… and made] their desires their guides” (Alwani, 1995:86). As a result, the western world “set out to spin for itself a web of speculative philosophy” (Alwani, 1995:85). As products of such a period, twentieth-century English literary texts inevitably contain a repertoire of such philosophies and ideologies. Hence, uncritical reception of such philosophies and ideologies by Muslim learners may amount to “submission to western intellectual, cultural, and institutional influences” (Alwani, 1995:87) and involve a danger of mental enslavement and cultural dislocation. Exposure to English literature concerns Alwani’s concept of ‘second reading’ (real-existential) which must be complemented by the ‘first reading’ (revelation) to create a civilized society that shares “knowledge worthy of preservation and further development or exchange” (Alwani, 1995:85). Therefore, this study will analyze selected twentieth-century English literary texts and mull over dominant ideas and beliefs they transmit as well as cultural influences they exert. It will identify ideas and values they promote and distinguish the ones that Muslims can embrace from those that they are religiously obligated to reject. Selected literary texts are: Joseph Conrad, Heart of Darkness (1899); T S Eliot, The Waste Land (1922); E M Forster A Passage to India (1924); George Orwell “Shooting an Elephant” (1936); Samuel Beckett, Waiting for Godot (1953). Since the above titles are taught at the undergraduate level, examining them from an Islamic perspective will inform a broad spectrum of practitioners. Moreover, such a critical exercise will facilitate meaningful cross-cultural and inter-civilizational dialogue by way of celebrating mutual similarities and understanding differences, which is in line with Alwani’s Sixth Discourse that contests “[o]utright rejection or wholesale acceptance” western sciences. This research will further develop what I discuss in “Teaching English Literature at IIUM: Islamic Perspectives on Selected Twentieth-Century Texts” (2016).